2019
DOI: 10.3280/ecag2019-001002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gender differences in the Italian traditional pizza consumption

Abstract: The studies on gender differences in food consumption have experienced a deep and remarkable development from several perspectives. Many studies have been addressed to highlight whether differences exist among males and females in purchasing behaviors or consumption for specific food products but no study pizza consumption segmented by gender has been carried out. This study evaluates gender differences in the consumption of traditional Italian pizza. For this purpose, a quantitative study was conducted on a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The correlation coefficients between PC2 and its respective determinants are 0.801 and 0.835. The findings support the theoretical expectation, revealing that men and women have different buying patterns, such as in the United States for organic food (Gundala et al, 2022); in Italy for Sicilian pizza consumption (Pappalardo et al, 2019); in Hungary for coffee, dairy products and health foods (Koroknay, 2021); in Mexico for low-calorie food (Manippa et al, 2017); and in Saudi Arabia for sweetened soft drinks (Benajiba, 2020). According to the survey, on average, more women preferred dates, compared to males.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The correlation coefficients between PC2 and its respective determinants are 0.801 and 0.835. The findings support the theoretical expectation, revealing that men and women have different buying patterns, such as in the United States for organic food (Gundala et al, 2022); in Italy for Sicilian pizza consumption (Pappalardo et al, 2019); in Hungary for coffee, dairy products and health foods (Koroknay, 2021); in Mexico for low-calorie food (Manippa et al, 2017); and in Saudi Arabia for sweetened soft drinks (Benajiba, 2020). According to the survey, on average, more women preferred dates, compared to males.…”
Section: Resultssupporting
confidence: 76%
“…Indeed, Gundala et al (2022) confirmed this conclusion for the US food consumers by demonstrating that men and women had different purchase intentions for organic foods. In addition, it was validated in Italy for Sicilian pizza consumption (Pappalardo et al, 2019) through differences in sensory attributes, such as smell, appearance, and crunchiness. In Hungary, women consumed more coffee and dairy products than men, who consumed fewer healthy foods (Koroknay, 2021).…”
Section: Consumer Decision-making and Segmentation Of Dates Market In...mentioning
confidence: 99%
“…Finally, despite the fact that many studies revealed the strong influence of socio-economic factors, such as gender, age, and lifestyle [40,41,42,43,44] on traditional and healthy food product consumption, no relationship or comparison with the earlier studies can be developed in as much as, in the authors knowledge, the literature on socio-economic differences for more health-beneficial processed meat consumers is still relatively scarce.…”
Section: Discussionmentioning
confidence: 99%